Determinan Faktor-faktor yang Mempengaruhi Kepesertaan Jaminan Sosial Ketenagakerjaan Sektor Formal - Hasiholan, Ardi; Tjiptoherijanto, Prijono (Jurnal Kebijakan Ekonomi, 2021)
Social security is functioned as a basic protection system for the community against the possibility of socio-economic risks that will arise in the future. One of the social security that is used as protection from the risks that society may face in the future is employment social security. The government encourages to increase the number of people who are protected by employment social security. This study aims to look at the determinants of the factors that affect employment social security participation specifically in the formal sector. By using the random effects model method and panel data consisting of five factors as independent variables from 123 branch offices, the researcher will examine what factors influence the participation of formal sector social security which is divided into two equations. More specific research was also conducted based on the branch office class category which was divided into three namely the main branch office class, the middle branch office class, and the pratama branch office class. Keywords: Labor Social Security; Supervision and Examination; Services; Panel Data.